Sandra Carli (Comp.) (2022). Historia de la Universidad de Buenos Aires. Tomo III (1945-1983). Ciudad Autónoma de Buenos Aires: Eudeba - Viera, Tomas (2024)
Revisión del libro Historia de la Universidad de Buenos Aires. Tomo III (1945-1983) por S. Carli